Ruthenium Carboxylate Complexes as Efficient Catalysts for the Addition of Carboxylic Acids to Propargylic Alcohols. Issue 18 (June 2015) - Jeschke, Janine; Gäbler, Christian; Korb, Marcus; Rüffer, Tobias; Lang, Heinrich
Abstract: Invited for the cover of this issue is the group of Heinrich Lang at the Technische Universität Chemnitz, Germany. The cover image shows the atom‐economical and highly selective addition of carboxylic acids to propargylic alcohols to give β‐oxopropyl esters. This conversion is catalyzed by ruthenium complexes, represented by the skater in our picture. Abstract : The kind of mononuclear ruthenium compounds presented in this work can be applied in many different fields of chemistry and materials science... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 2939 ff .